2011
DOI: 10.2298/zmspn1120019j
|View full text |Cite
|
Sign up to set email alerts
|

Presence of deoxynivalenol in small-grain samples from 2009/10 harvest season

Abstract: Fusarium head blight (FHB) is present in all growing regions of small grains and causes significant losses in yield and grain quality. In our environmental conditions, dominant species is Fusarium graminearum Group 2. During 2009/10 there was a significant Fusarium infestation on wheat, barley and triticale. The aim of this study was to examine the contents of deoxynivalenol (DON) in cereal samples taken after 2009/10 harvest season. We analyzed 22 NS varieties of small grains from Rimski Šančevi, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…An exception was the year 2014 and, to some extent, the year 2010. The results obtained by Kos et al [80] and Jajic et al [81,82] indicated that weather conditions recorded in 2014 and 2010, in terms of air temperature and the amount of precipitation, had a significant influence on DON occurrence. Samples analysed in 2014 showed a DON prevalence of 96.2% ( n = 640), with 45.6% of the samples exceeding the EU MRL (Table 3), while samples analysed in 2010 showed a DON prevalence of 73.5% ( n = 310), with 6.8% of the samples exceeding the EU MRL (Table 3).…”
Section: Principal Mycotoxins In Food and Feed In Serbiamentioning
confidence: 99%
“…An exception was the year 2014 and, to some extent, the year 2010. The results obtained by Kos et al [80] and Jajic et al [81,82] indicated that weather conditions recorded in 2014 and 2010, in terms of air temperature and the amount of precipitation, had a significant influence on DON occurrence. Samples analysed in 2014 showed a DON prevalence of 96.2% ( n = 640), with 45.6% of the samples exceeding the EU MRL (Table 3), while samples analysed in 2010 showed a DON prevalence of 73.5% ( n = 310), with 6.8% of the samples exceeding the EU MRL (Table 3).…”
Section: Principal Mycotoxins In Food and Feed In Serbiamentioning
confidence: 99%